2018
DOI: 10.1021/acs.jafc.8b04241
|View full text |Cite
|
Sign up to set email alerts
|

Methionine Promotes Milk Protein and Fat Synthesis and Cell Proliferation via the SNAT2-PI3K Signaling Pathway in Bovine Mammary Epithelial Cells

Abstract: Methionine (Met) plays a critical regulatory role in milk production, however, the molecular mechanism of action of Met is largely unknown. This study therefore aimed to investigate the influence of Met on milk synthesis in and proliferation of bovine mammary epithelial cells (BMECs) and explore the underlying mechanism. BMECs cultured in fetal bovine serum (FBS) free Dulbecco’s modified eagle’s medium (DMEM)/F-12 medium were treated with Met (0, 0.3, 0.6, 0.9, and 1.2 mM). Results showed that Met (0.6 mM) sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 40 publications
8
58
1
Order By: Relevance
“…Once the mTOR system is activated by AA sufficiency, mTOR and its downstream molecules (S6K1 and 4EBP1) are phosphorylated (44,45) . In the study, alterations of the protein expression of mTOR-related proteins by Met supplementation were in accordance with previous findings in BMEC supplemented with Met (29,42) . However, we found that SARS knockdown depressed mTOR activation under Met stimulation, which is consistent with the inhibition of the mTOR activation by leucyl-tRNA synthetase knockdown in the HEK293T cells (22) and BMEC (23) in response to leucine.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Once the mTOR system is activated by AA sufficiency, mTOR and its downstream molecules (S6K1 and 4EBP1) are phosphorylated (44,45) . In the study, alterations of the protein expression of mTOR-related proteins by Met supplementation were in accordance with previous findings in BMEC supplemented with Met (29,42) . However, we found that SARS knockdown depressed mTOR activation under Met stimulation, which is consistent with the inhibition of the mTOR activation by leucyl-tRNA synthetase knockdown in the HEK293T cells (22) and BMEC (23) in response to leucine.…”
Section: Discussionsupporting
confidence: 92%
“…Studies reported that the lactation performance (especially the yield of milk and milk protein and milk protein concentration) in dairy cows receiving supplemental dietary Met (25-35 g/d) at early lactation (39) or postruminal infusion of rumen-protected Met (60 g/d) during the peripartal period in vivo (40) was both significantly increased compared with those in groups without Met supplementation. Our study showed that Met supplementation at the concentration of 0•6 mM can significantly promote the casein synthesis and activate mTOR signalling, which were similar to several previous studies (29,41,42) .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additional nutritional compounds beside FA can regulate SREBP1 in bovine mammary epithelial cells, such as methionine [277] which is partly mediated by FABP5 [278]. Alongside milk fat synthesis, SREBP1 plays other roles in dairy cows, such as the demonstrated role in regulating homeostasis of the sodium/iodide symporter in mammary epithelial cells, as observed in humans [279], and it is involved in liver lipid metabolism in peripartum cows [263], including regulation of TAG synthesis in bovine hepatocytes [280,281].…”
Section: Sterol Regulatory Element-binding Proteinsmentioning
confidence: 99%
“…Increasing evidence suggests that Cyclin D1 level decreases in response to cell cycle arrest, affecting cell homeostasis and resulting in the termination of various cellular processes [26,27]. In previous studies, percentages of cells in the S or G2/M phases increased, while cell proliferation decreased with a decrease in Cyclin D1 level, ultimately affecting milk protein and fat synthesis [28,29]. In our study, loss of UFL1 induced a decrease in Cyclin D1 level and an increase in the rate of apoptosis, thereby disrupting homeostasis of mammary epithelial cells.…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 93%